THE ROLES OF PUBLIC FIGURE IN FOOD BRANDING: A CASE STUDY - Rahayuningsih, Handayani (Jurnal Manajemen Bisnis, 2019)
To make the experiences of visiting tourist destination become tangible, tourists are inclined to bring some souvenirs for their family and friends. Such big target market is enough reason to make businesses which provide souvenirs such as goods and foods in the tourist destinations. At the moment, there is an ongoing trend in Indonesia which uses celebrity or famous public figures’ names as a part of the souvenirs’ marketing appeal. Malang Strudel, Jogja Scrummy, and Surabaya Snowcake are a few examples of foods, especially pastries, as souvenir that are specifically marketed for the visitors of a particular city, and use famous actors and  actress’  as owner  and  their  brand ambassadors. The  construction  of  foods identity and products branding of food as souvenir were the focus of this research. The data were collected through interview, documentation, and observation. The results indicate that public figures are extremely important in creating the identity of food as the souvenir of a particular city, although the product itself is not originally from the city. Moreover, tourists who buy the food as souvenir were influenced by the public figures’ name.